1997
DOI: 10.1159/000262398
|View full text |Cite
|
Sign up to set email alerts
|

A Method for the Quantitative Site-Specific Study of the Biochemistry within Dental Plaque Biofilms Formed in vivo

Abstract: The study of plaque biofilms in the oral cavity is difficult as plaque removal inevitably disrupts biofilm integrity precluding kinetic studies involving the penetration of components and metabolism of substrates in situ. A method is described here in which plaque is formed in vivo under normal (or experimental) conditions using a collection device which can be removed from the mouth after a specified time without physical disturbance to the plaque biofilm, permitting site-specific analysis or exposure of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 11 publications
4
53
0
3
Order By: Relevance
“…This more open architecture, combined with the synthesis of a matrix comprised of a diverse range of exopolymers, creates a complex environment for predicting the penetration and distribution of molecules within plaque. Uneven patterns of penetration of radiolabelled fluoride, sucrose and phosphate were found in plaque generated naturally on an in situ biofilm model in volunteers [Robinson et al, 1997], while the diffusion of glucans of increasing molecular size was retarded in laboratory mixed culture biofilms [Thurnheer et al, 2003]. Bacterial metabolism ensures that gradients develop in parameters that are critical to microbial growth (nutrients, pH, oxygen); the gradients in pH are also responsible for enamel demineralization.…”
Section: Structure Of Dental Plaquementioning
confidence: 99%
“…This more open architecture, combined with the synthesis of a matrix comprised of a diverse range of exopolymers, creates a complex environment for predicting the penetration and distribution of molecules within plaque. Uneven patterns of penetration of radiolabelled fluoride, sucrose and phosphate were found in plaque generated naturally on an in situ biofilm model in volunteers [Robinson et al, 1997], while the diffusion of glucans of increasing molecular size was retarded in laboratory mixed culture biofilms [Thurnheer et al, 2003]. Bacterial metabolism ensures that gradients develop in parameters that are critical to microbial growth (nutrients, pH, oxygen); the gradients in pH are also responsible for enamel demineralization.…”
Section: Structure Of Dental Plaquementioning
confidence: 99%
“…Recent work has indicated that much of this appears to be located in the outer regions of the plaque biofilm layer Robinson et al, 1997]. It may be released into plaque from fluoride-treated enamel [Arai et al, 2000].…”
mentioning
confidence: 99%
“…Porphyromonas gingivalis and Fusobacterium nucleatum strongly believed as major pathogens in the etiology of adult periodontitis 1) . However, Antibacterial agents are also widely used, but problems with general efficacy due to access of topical agents to plaque and the possibility of development of bacterial resistance mean alternative strategies are desirable to control plaque and treat gingivitis and periodontal disease 2,3) .…”
Section: Zakeri Mahdi Et Almentioning
confidence: 99%